Growth and phenology of three Andean potato varieties (Solanum tuberosum L.) under water stress (2016)
The water-deficit stress has a negative effect on the growth and development of plants, reducing the yield of crops. This study evaluated the effect of a water deficit on the growth and phenology of potato (Solanum tuberosum L.) varieties Diacol Capiro, Pastusa Suprema and Esmeralda. Plants that were starting tuberization were subjected to a water deficit by suspension of irrigation until reaching a foliar water potential of -2.0 MPa; later the plants were re-irrigated and recovered. The water deficit decreased the flowering time in ‘Diacol Capiro’, the development of leaves and maturation of fruits in ‘Esmeralda’ and the development of leaves and formation of lateral shoots in ‘Pastusa Suprema’. In the three varieties, the water deficit did not induce a significant reduction in the stem length, the number of leaves per stem and per site or the number of main stems per site. The plants demonstrated responses related to escape and evasion mechanisms during the water deficit through the adjustment of the metabolism in order to reduce the duration of the phenological stages. The duration of the biological cycle for the three varieties was 148 days, with a requirement of 1,850 GDD. There were no differences in the potential yield, probably due to the short duration of the stress period. The three varieties demonstrated plasticity when modifying the phenology in response to the drought period.